2019
DOI: 10.1080/21691401.2019.1646750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymorphism on IL1A to cancer susceptibility: Evidence based on 34,016 subjects

Abstract: IL-1a is closely related to the development and metastasis of cancer, and its polymorphisms have been reported affecting the susceptibility of malignancy tumors, yet the conclusions are controversial. Present an overall meta-analysis was performed to reach more general findings. Relevant literature was searched from Google Scholar, Web of Science, PubMed, EMBASE, CNKI database and Wanfang database, and the association among polymorphism and cancer risk was appraised by counting ORs and 95% CIs of overall and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Another point is that IL-1α has been shown to act by recruiting adhesion, invasion, and angiogenesis molecules in pancreatic cancer cell lines co-cultured with fibroblasts (43). In addition, an important feature that demonstrates the centrality of this gene in tumor progression is its polymorphisms, where numerous SNPs of this gene were detected in different populations that can increase the predisposition and malignancy of different tumor types (44).…”
Section: Discussionmentioning
confidence: 99%
“…Another point is that IL-1α has been shown to act by recruiting adhesion, invasion, and angiogenesis molecules in pancreatic cancer cell lines co-cultured with fibroblasts (43). In addition, an important feature that demonstrates the centrality of this gene in tumor progression is its polymorphisms, where numerous SNPs of this gene were detected in different populations that can increase the predisposition and malignancy of different tumor types (44).…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphisms with proved functional activity are VEGFA (rs699947, rs833061, rs25648, rs1005230), IL-1β (rs1143634, rs16944), IL-1α (rs1800587) and IL-6 (rs1800795, rs1800797) (14)(15)(16)(17)(18)(19)(20)(21). Candidate gene studies as well as moderate-sized genome-wide association studies (GWAS) highlight the important role of these polymorphisms in BC risk and aggressiveness (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), although substantial heterogeneity across studies exists. The currently available results are inconsistent in terms of different ethnicity and cancer stage; therefore, it is necessary to further investigate the role of VEGFA, IL-1β, IL-1α and IL-6 gene polymorphisms in breast carcinogenesis and cancer progression.…”
Section: Association Of Angiogenesis and Inflammation-related Gene Fumentioning
confidence: 99%
“…Overexpression of the IL-1α promotes tumour invasiveness and metastasis by inducing the expression of angiogenic genes and growth factors (12). A large meta-analysis performed by Xia et al (30) showed that the IL-1α rs1800587 C allele and CC genotype are associated with increased cancer risk in general. The studies which investigated the associations between IL-1α rs1800587 polymorphism and BC survival are presented in Table VII.…”
Section: Pfs Mfs Os -------------------------------------------------mentioning
confidence: 99%